Nonsteroidal anti-inflammatory drug-induced colopathy: an uncommon cause of positive immunochemical faecal occult blood test in the program for colorectal cancer screening - Smolović, Brigita; Vučković, Ljiljana; Borozan, Sanja; Vukčevič, Batrić (Vojnosanitetski pregled, 2021)
Introduction. Nonsteroidal anti-inflammatory drug-induced colopathy is an uncommon condition associated with the long-term use of enteric-coated and slow-release nonsteroidal anti-inflammatory drugs. This paper presents a case of colopathy showing no symptoms or signs, discovered by a positive immunochemical faecal occult blood test. Case report. Performed within the framework of the National Program for Screening of Colorectal Cancer, the immunochemical faecal occult blood test was positive in a 56-year-old female patient. The colonoscopy revealed three lesions in the right colon: one erosion-ulceration and two concentric "diaphragm-like" strictures passable by the endoscope. The patient reported that she had been taking diclofenac 100 mg twice a day for the past seven years. After withdrawing the offending drug, the second colonoscopy indicated a marked improvement in the colonic mucosa while the "diaphragm-like" strictures persisted. Conclusion. The cases of nonsteroidal anti-inflammatory drug-induced colopathy are likely to become more frequent. It would be, therefore, advisable to consider the long-term use of such drugs as being a possible factor that leads to mucosal injury, particularly in the right colon, as well as being a rare reason for a positive immunochemical faecal occult blood test.